Tom Clancy zero hour [large type] - Bentley, Don; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan Jr. novel, 2022)
"When the leader of North Korea is catastrophically injured, his incapacitation inadvertently triggers a "dead-man's switch," activating an army of sleeper agents in South Korea and precipitating a struggle for succession. Jack Ryan, Jr. is in Seoul to interview a potential addition to The Campus. But his benign trip takes a deadly turn when a wave of violence perpetrated by North Korean operatives grips South Korea's capital. A mysterious voice from North Korea offers Jack a way to stop the peninsula's rush to war, but her price may be more than he can afford to pay"--